2016
DOI: 10.1038/srep34238
|View full text |Cite
|
Sign up to set email alerts
|

MiR-24-BIM-Smac/DIABLO axis controls the sensitivity to doxorubicin treatment in osteosarcoma

Abstract: Emerging evidence shows that microRNAs (miRNAs) act as critical regulators in the progression and chemoresistance of multiple tumors, including osteosarcoma (OS). In this study, we found that the level of miR-24 was increased in OS patients’ serum, tumor tissues and OS cell lines. Furthermore, we found that knockdown of miR-24 by its specific inhibitors significantly increased the therapeutic effect of doxorubicin (DOX) on OS cell lines (MG-63 and HOS). Moreover, miR-24 inhibitors resensitized the doxorubicin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 40 publications
1
20
0
1
Order By: Relevance
“…At present, chemotherapy is still an effective treatment to kill OS cells and prolong the life of patients. However, repeated use of chemotherapeutic drugs induces inevitable multiple drug resistance in cancer cells (2,3). Reliable strategies are urgently required to reverse the multiple drug resistance of OS.…”
Section: Introductionmentioning
confidence: 99%
“…At present, chemotherapy is still an effective treatment to kill OS cells and prolong the life of patients. However, repeated use of chemotherapeutic drugs induces inevitable multiple drug resistance in cancer cells (2,3). Reliable strategies are urgently required to reverse the multiple drug resistance of OS.…”
Section: Introductionmentioning
confidence: 99%
“…increasing research in recent years has verified that miRNAs play important regulatory roles in genesis and development of tumor cells. miRNAs have their own expression profiles in different malignant tumor tissues, as is demonstrated (11). Furthermore, it is also revealed that multiple miRNA molecules participate in regulating important biological processes of cancer cells through silencing expression of cancer cell growth-related genes, thus indirectly exerting tumor-promoting and tumorsuppressing functions (8).…”
Section: Discussionmentioning
confidence: 86%
“…However, transfection with TAZ plasmid abolished the effect of miR-26b ( Figure 5B). As the downstream of cytochrome c release, we observed that combination with cisplatin and miR-26b induced significant cleavage of caspase-9 and caspase-3 which are effectors of intrinsic apoptosis 22,23 (Figure 5C). And finally, restoration of miR-26b expression increased the apoptotic rate of PC9/ R and A549/R cells which were under the cisplatin treatment through suppression of TAZ ( Figure 5D).…”
Section: Restoration Of Mir-26b Expression Targets Taz To Increase Thmentioning
confidence: 95%